The Students' Perceptions on Teacher "Performances" in Teaching English - Agus Setiawan (INTERACTION: Jurnal Pendidikan Bahasa, 2020)
This study was conducted to find out how the students' perceptions on English teachers. The problem focuses on students' perceptions of the teacher's learning methods while learning the learning takes place, and an effective learning process with student learning outcomes gained. In this study the authors take respondents to get data that is as much as 4 respondents, where the one respondent is an English teacher and 3 other respondents are students. Researchers conducted interviews on each respondent. In this case, the teacher to know the methods used in the learning process and the students to know how performance teacher in the learning process. The method used in this research is descriptive design. This study reveals that teachers' performance in English learning is good, where teachers can apply motivation of students learning, learning model, classroom management, use of facilities, and student experience well. And for the learning method, the teacher does not use special methods in the learning process, but the teacher learning model is applied more to adaptation to the material taught to students. Nevertheless, the teacher will improve the methods in learning and innovate for the success of the learning process.